2017
DOI: 10.1007/s00330-017-5172-6
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiography prior to catheter ablation could be avoided in atrial fibrillation patients with a low risk of stroke and without filling defects in the late-phase MDCT scan: A retrospective analysis of 783 patients

Abstract: • MDCT can help detect the presence of LAA thrombus. • TEE can be avoided when late-phase MDCT shows no filling defect. • TEE is required in patients whose MDCT images indicate thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…The baseline characteristics of the included studies are shown in Table 1 . 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 Seventeen studies (63%) had a prospective design, and 10 studies (37%) had a retrospective design. Nineteen studies (70%) were performed with patients scheduled for pulmonary vein isolation (PVI), 4 studies (15%) were performed with patients recently experiencing stroke, 1 study was performed with patients scheduled to direct current cardioversion, and the remaining 3 studies had mixed populations.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies are shown in Table 1 . 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 Seventeen studies (63%) had a prospective design, and 10 studies (37%) had a retrospective design. Nineteen studies (70%) were performed with patients scheduled for pulmonary vein isolation (PVI), 4 studies (15%) were performed with patients recently experiencing stroke, 1 study was performed with patients scheduled to direct current cardioversion, and the remaining 3 studies had mixed populations.…”
Section: Resultsmentioning
confidence: 99%
“…Исследование Z. Zhai и соавт. показало, что отсутствие дефекта наполнения в поздней фазе мультиспиральной КТ позволяет исключить наличие тромба УЛП и избежать ЧпЭхоКГ перед катетерной абляцией у пациентов с ФП с низким риском инсульта (балл по шкале CHA2DS2-VASc ≤3) [14].…”
Section: принятые сокращенияunclassified
“…The result shows that a delayed imaging method of cardiac CT significantly improved the specificity (1.00 vs. 0.89; P <0.05) and positive posterior probability (95.76% vs. 19.11%; P <0.05) compared with TEE and may save the patients from an excess TEE. Also, preprocedural TEE can be avoided for patients with AF, who have a low risk of stroke and no filling defect on delayed CT scans 93. In addition, for the recently developed TAVR, multislice CT can detect the geometry of the implanted valve stent and potentially optimize size selection during TAVR 94.…”
Section: Imaging In Structural Heart Diseasementioning
confidence: 99%